2011
DOI: 10.3791/2540
|View full text |Cite
|
Sign up to set email alerts
|

Expansion, Purification, and Functional Assessment of Human Peripheral Blood NK Cells

Abstract: Natural killer (NK) cells play an important role in immune surveillance against a variety of infectious microorganisms and tumors. Limited availability of NK cells and ability to expand in vitro has restricted development of NK cell immunotherapy. Here we describe a method to efficiently expand vast quantities of functional NK cells ex vivo using K562 cells expressing membrane-bound IL21, as an artificial antigen-presenting cell (aAPC). NK cell adoptive therapies to date have utilized a cell product obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 11 publications
4
149
0
Order By: Relevance
“…Resting NK cells were cultured in the presence of 100 IU of IL2 for 48 h to obtain activated NK cells. Higher levels of NK cell activation were achieved by coculturing freshly isolated peripheral blood lymphocytes with engineered K562 cells, K562-Clone9-mb21, as described in detail before 37,38 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resting NK cells were cultured in the presence of 100 IU of IL2 for 48 h to obtain activated NK cells. Higher levels of NK cell activation were achieved by coculturing freshly isolated peripheral blood lymphocytes with engineered K562 cells, K562-Clone9-mb21, as described in detail before 37,38 .…”
Section: Methodsmentioning
confidence: 99%
“…The expansion procedure is described briefly as follows: First, primary human NK cells were isolated by negative selection using EasySepHuman NK cell enrichment kit (Stemcell technologies,Vancouver,Canada). Then, primary NK cells were admixed in a 1:2 ratio with 100 Gr irradiated K562-Cl9-mb21cells, which express CD86, 4-1BBL and mIL21 on their surface, and cultured in NK cell expansion medium 38 . Cells were spun down at 400g for 5 min, and the culture medium was renewed every 3 days with fresh culture medium, keeping the cell density at 250,000 cells per ml after every subculture.…”
Section: Methodsmentioning
confidence: 99%
“…K562-expanded NK cells show potential defects in CCR7-mediated homing to lymph nodes. 129 Modification of K562 feeder cells to transfer CCR7 to NK cells via trogocytosis transiently increases NK cell CCR7 expression and improves homing to LNs of athymic mice. 130 Culture with irradiated EBV LCL reduces CD62L-mediated homing to marrow and secondary lymphoid tissues, which can be improved by adding nicotinamide to the culture.…”
Section: Lymphoyte Contamination Of the Graft T-cell Contaminationmentioning
confidence: 99%
“…NK cells expanded with genetically modified K562 cells contain predominantly CD56 ϩ /16 ϩ bright NK cell populations, which do not express CCR7, a chemokine receptor that is known to facilitate NK cell homing to lymph nodes. 67 Although IL-18 can up-regulate CCR7, it does so in only a minority of NK cells. 68 Somanchi et al recently demonstrated that mbIL-21-expressing K562 feeder cells can be further genetically modified to express other transgenes, the products of which can be rapidly and transiently expressed in NK cells via trogocytosis by coculturing with expanded NK cells.…”
Section: Homingmentioning
confidence: 99%